2003
DOI: 10.1093/mutage/geg021
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding of polycyclic aromatic hydrocarbons in a human bronchial epithelial cell line treated with diesel and gasoline particulate extracts and benzo[a]pyrene

Abstract: Particulate matter of vehicle exhaust is known to contain carcinogenic compounds such as polycyclic aromatic hydrocarbons (PAH) and is suggested to increase lung cancer risk in humans. This study examines the differences in diesel and gasoline-derived PAH binding to DNA in a human bronchial epithelial cell line (BEAS-2B). Particulate matter (PM) of gasoline exhaust was collected from passenger cars on filters and semi-volatile compounds on polyurethane foam (PUF). The soluble organic fraction (SOF) extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
23
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
2
23
0
3
Order By: Relevance
“…In particular, PM1 was responsible for approximately 80% of the observed effects at various 239 sampling localities (Novak et al, 2014), and the fine particles generally showed higher mutagenicity 240 (Claxton et al, 2004;Claxton and Woodall, 2007b;Lemos et al, 2012). The gas phase mutagenicity was very 241 low and often indeterminable, with the exception of particular sampling sites such as industrial sites (Du 242 Four et al, 2005) and exhaust emissions from gasoline-and diesel-powered passengers cars (Pohjola et al, 2003a;Pohjola et al, 2003b). The contribution of the gas phase with respect to the particulate phase seems 244 to be higher during summer and related to the major PAHs content (Du Four et al, 2004;Kennedy et al, 245 2010).…”
mentioning
confidence: 99%
“…In particular, PM1 was responsible for approximately 80% of the observed effects at various 239 sampling localities (Novak et al, 2014), and the fine particles generally showed higher mutagenicity 240 (Claxton et al, 2004;Claxton and Woodall, 2007b;Lemos et al, 2012). The gas phase mutagenicity was very 241 low and often indeterminable, with the exception of particular sampling sites such as industrial sites (Du 242 Four et al, 2005) and exhaust emissions from gasoline-and diesel-powered passengers cars (Pohjola et al, 2003a;Pohjola et al, 2003b). The contribution of the gas phase with respect to the particulate phase seems 244 to be higher during summer and related to the major PAHs content (Du Four et al, 2004;Kennedy et al, 245 2010).…”
mentioning
confidence: 99%
“…1-NP, one of the most abundant polycyclic aromatic hydrocarbons, is a product of incomplete diesel and gasoline combustion (1,29,30). There are two known pathways by which 1-NP is metabolized: nitro reduction (Scheme 1) and C-hydroxylation.…”
mentioning
confidence: 99%
“…This is in keeping with the ability of the quinones to participate in redox cycling reactions after cellular uptake, while PAHs need to be enzymatically converted to oxy-derivatives before being rendered functionally active [32,33]. Previously published studies demonstrating that environmental polycyclic aromatic hydrocarbons, including DEP extracts, are capable of inducing cytochrome P450 1A1 and 1B1 expression in human macrophages and bronchial epithelial cells supports this notion [1,34,35]. While evidence has been provided that this is also true in BEAS-2B cells, the same needs to be demonstrated for RAW 264.7 cells.…”
mentioning
confidence: 56%